Security System Based on IoT in Karyawangi Parongpong Village: Design Phase - Lita Lidyawati; Dani Rusirawan; Lisa Kristiana; Narisha Kalya Mahsa (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2021)
Security is always an issue both in individuals and communal attentions. Any forms of threats and crimes that occur in the village area of Karyawangi Parongpong, such as motor vehicle theft, violence, drug abuse, gambling, and others are caused by a lack of supervision from local authorities. The limitation of surveillance distance is one of the problems. Thus, an effective and appropriate security system in a place is indispensable. In this paper, the design of the security system using IoT modules and ESP32 Camera, will be elaborated for karyawangi Parongpong's village. The system secures a village environment by detecting an intruder on the road, triggering Passive Infra Red (PIR) sensor, capturing all activities with ESP32 camera, and then sending data to a smart mobile phone through with Telegram application. These service activities were aimed at the improvement of security systems and increase knowledge of technology advances for rural communities in the Karyawangi Village environment, especially in security systems based on IoT.